The integration of facebook as an ict- supporting tool into English language teaching teachers’ attitudes and uses - A case in the Mekong delta - Dương, Thị Thanh Phương (Can Tho University, 2015)
Aimed to investigate the present situation of intergrating the social network site - Facebook as an information and communication technology (ICT) supporting tool into Enlgish language teaching in term of teachers' attituses and uses